'Stick Them to the Cross': Anti-Trafficking Apps and the Production of Ignorance. Issue 3 (3rd July 2022) - Mendel, Jonathan; Sharapov, Kiril
ABSTRACT: There is a long history of ignorance production around trafficking in human beings. A proliferation of anti-trafficking apps plays an important role in the reinforcement of this ignorance. Anti-trafficking apps work in different ways from other (mis)information tools, but there is a lack of academic research on the topic. This paper addresses this gap through an agnotological approach focusing on how ignorance is produced and becomes productive, rather than seeing ignorance as just a lack of knowledge. We investigate how anti-trafficking apps are used to manipulate (mis)understandings of and responses to human trafficking by enabling new types of awareness raising, user participation and ignorance production. The networking of ignorance that this allows – and the integration of this into new aspects of everyday life – illustrates de Goede's warning that "the network is problematic as a security technique…because, ultimately, it has no outside".